Hepatic stellate cell activation and senescence induced by intrahepatic microbiota disturbances drive progression of liver cirrhosis toward hepatocellular carcinoma. Issue 1 (7th January 2022) - Liu, Boyuan; Zhou, Zewei; Jin, Yu; Lu, Jinying; Feng, Dongju; Peng, Rui; Sun, Hua; Mu, Xiaoxin; Li, Changxian; Chen, Yun
Abstract : Background: The significance of the relationship between the microbiota and diseases is increasingly being recognized. However, the characterization of tumor microbiome and their precise molecular mechanisms through which microbiota promotes hepatocellular carcinoma (HCC) development are still unclear. Methods: The intrahepatic microbiota was investigated from tumor, normal adjacent tissues in 46 patients with HCC and normal hepatic tissues in 33 patients with hemangioma by 16S rRNA gene sequencing. Taxonomic composition differences in patients were evaluated using Linear discriminant analysis Effect Size (LefSe) and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) to predict microbial functional pathways. Associations between the most relevant taxa and clinical characteristics of HCC patients were analyzed by Spearman rank correlations. The effects of microbe on hepatic stellate cells (HSCs) activation and HCC progression were examined. Results: We observed intrahepatic microbiota disturbances by reduced microbial diversity in HCC. The tumor microbiota of the HCC patients with cirrhosis showed higher abundance of Stenotrophomonas maltophilia (S. maltophilia) . S. maltophilia provoked senescence-associated secretory phenotype (SASP) in HSCs by activating TLR-4-mediated NF-κB signaling pathway, which in turn induced NLRP3 inﬂammasome complex formation and secreted various inflammatory factors in the liver, thus facilitating HCC progression in mice. Moreover, signs of SASP were also observed in the HSCs in the area of HCC with higher S. maltophilia enrichment arising in patients with cirrhosis. Conclusions: Our analysis of the hepatic microbiota revealed for the first time that patients with HCC exhibited a dysbiotic microbial community with higher S. maltophilia abundance, which induced the expression SASP factors of HSCs and cirrhosis in the liver, concurring in the process of hepatocarcinogenesis.